British and Japanese military leadership in the Far Eastern War, 1941-1945 - Bond, Brian; Tachikawa, KyÕoichi, 1966- (Cass series--military history and policy, 2004)
Some sixty years after the Far Eastern War ended, this innovative new collection brings together five distinguished UK-based scholars and five from Japan to reappraise their respective country's leadership in the Malaya and Burma campaigns. This leadership is analyzed on various levels, ranging from the grand strategic to operational. The Japanese contributors examine the reasons for their forces, brilliant advances in 1941-42, whereas the British writers have to account for the disastrous defeat, characterized by the poor leadership of senior commanders such as Bennett and Percival. Be.